9x-13=x+5

Simple and best practice solution for 9x-13=x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-13=x+5 equation:


Simplifying
9x + -13 = x + 5

Reorder the terms:
-13 + 9x = x + 5

Reorder the terms:
-13 + 9x = 5 + x

Solving
-13 + 9x = 5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-13 + 9x + -1x = 5 + x + -1x

Combine like terms: 9x + -1x = 8x
-13 + 8x = 5 + x + -1x

Combine like terms: x + -1x = 0
-13 + 8x = 5 + 0
-13 + 8x = 5

Add '13' to each side of the equation.
-13 + 13 + 8x = 5 + 13

Combine like terms: -13 + 13 = 0
0 + 8x = 5 + 13
8x = 5 + 13

Combine like terms: 5 + 13 = 18
8x = 18

Divide each side by '8'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| 4(4+4x)=-4+6x | | 2(n-9)=6+n-3(1+n) | | 6ln(x+3)-3lnx= | | 8(5t+1)-15=t-(t+6) | | 55(x+1)=48 | | 6(1-7x)=6-8x | | 15*7+(10-7)=141 | | 6(6t+1)-9=t-(t+2) | | 2y-3=12y | | 3k^2+2k-3=0 | | y=3x-10 | | -x+5(-6x+4)=-197 | | 5x+5=59 | | 2(3n-1)= | | 5p-7=55-5p | | -8-8p=-p-8p-5 | | 55t*2t=6.50+405.50 | | 1/4f-4=1 | | -97=-7-6(5-5x) | | 63=p-19 | | 4y-9+40=5y | | 1/2(4x)(6x-5)= | | y=-3cospix+2 | | V+1=-7-5v+2v | | 4f=64 | | 3x(4x-8)=0 | | 3(x-2)=6x-12/3 | | 15903*5/2285.45 | | 12x*24y=12(x*2y) | | 3-7x=-12+8x | | .2x+8(1000-x)=.65(1000-x) | | 2385.45/15903*5 |

Equations solver categories